MiRNAs function in the development of resistance against doxorubicin in cancer cells: targeting ABC transporters - Lu, Xin-Yan; Jin, Hongxu (Frontiers in Pharmacology, 2024)
Resistance to chemotherapeutic agents poses a significant challenge in cancer treatment, particularly with doxorubicin, a widely used drug for various cancers, including breast cancer, leukaemia, osteosarcoma, and gastrointestinal cancers. This review aims to elucidate the critical role of microRNAs (miRNAs) in the development of doxorubicin resistance, focusing on their interactions with ATP-binding cassette (ABC) transporters. Despite extensive research, the molecular mechanisms governing doxorubicin resistance still need to be completed, particularly regarding the regulatory influence of miRNAs on ABC transporter expression. By analyzing current literature, this review identifies a notable gap: the lack of comprehensive insight into how specific miRNAs modulate the expression and activity of ABC transporters in cancer cells, contributing to doxorubicin resistance. We systematically examine recent findings on the interplay between miRNAs and ABC transporters, providing a detailed assessment of potential therapeutic strategies that leverage miRNA modulation to overcome drug resistance. Ultimately, this review underscores the significance of integrating miRNA research into existing therapeutic frameworks to enhance the efficacy of doxorubicin in cancer treatment.